Antioxidant Activity of n-Hexane, Ethyl Acetate and Ethanol Extract from Lakoocha Leaves (Artocarpus lacucha Buch.-Ham) using DPPH Method - Mardiana; Zaitun Hasibuan, Poppy Anjelisa (Indonesian Journal of Pharmaceutical and Clinical Research, 2018)
This study aimed to investigate phytochemical screening and antioxidant activity of n–hexane, ethyl acetate and ethanol extract from lakoocha leaves. The powdered simplicia was macerated with n–hexane, ethyl acetate and ethanol 96% successively, filtered, then concentrated using rotary evaporator to obtain n–hexane extract, ethyl acetate extract and ethanol extract. Phytochemical screening and antioxidant activity was performed against these extracts. Antioxidant activity was determined by DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging method using ultraviolet-visible spectrophotometer at wavelength of 516 nm after incubated for 60 minutes in dark place. Quercetin was used as positive control. The result of phytochemical screening showed n-hexane extract contains steroid, ethyl acetate extract contain steroid, tannin, glycoside, flavonoid and saponin, whereas ethanol extract contain tannin, glycoside, flavonoid and saponin. The IC50 value of n–hexane, ethyl acetate and ethanol extract was 1062.03±1.42 ppm, 323.18±0.02 ppm and 99.23±0.07 ppm respectively, whereas for quercetin was 2.32±0.01 ppm. This study showed that ethanol extract had antioxidant activity with strong category whereas n-hexane extract and ethyl acetate extract had inactive antioxidant activity with very weak categories. Keyword: Antioxidant Activity, DPPH, Lakoocha leaf